Bromine‐Substituted Cation Anchoring to Suppress Ion Migration in Alternating Cations Intercalation‐Type Perovskite for Stable X‐Ray Detection - Lijun Xu; Qianwen Guan; Huang Ye; Jianbo Wu; Hang Li; Yaru Geng; Chengshu Zhang; Zeng‐Kui Zhu; Zhangtong Han; Qiuxiao Yin; Junhua Luo (Small Structures)
Metal halide perovskites have emerged as excellent direct X‐ray detection materials owing to their large mobility‐lifetime product, strong radiation absorption, and low‐cost preparation. However, it is still a challenge to achieve stable X‐ray detection due to the limitations associated with severe ion migration under high voltage bias. Herein, based on a bromine substitution strategy to suppress ion migration, a 2D alternating cations intercalation‐type (ACI) perovskite, (R‐MPA)(BrEA)PbBr4 (1, R‐MPA = methylphenethylamm‐onium; BrEA = 2‐bromoethylamine) is reported to achieve X‐ray detection. Specifically, introducing Br atom forms additional intermolecular interactions (i.e., Br···π) and enhances hydrogen bonding interactions, greatly improving the structure stability. Based on this enhanced interaction, 1 presents a higher activation energy of ion migration (1.05 eV) than that of (R‐MPA)EAPbBr4 resulting in a lower dark current drift of 9.17 × 10−8 nA cm−1 s−1 V−1, revealing that suppression of ion migration. Consequently, the 1‐based detector shows a high sensitivity of 2653.7 μC Gy−1 cm−2 and, most importantly, outstanding operational and environmental stability, maintaining ≈91% of its initial sensitivity at 50 V bias after 90 days in the air. This work demonstrates an efficient strategy for introducing halogen interactions via ACI to suppress ion migration for stable X‐ray detection.